Patterns‐of‐care and health economic analysis of robot‐assisted radical prostatectomy in the Australian public health system. (1st October 2015) - Basto, Marnique; Sathianathen, Niranjan; te Marvelde, Luc; Ryan, Shane; Goad, Jeremy; Lawrentschuk, Nathan; Costello, Anthony J.; Moon, Daniel A.; Heriot, Alexander G.; Butler, Jim; Murphy, Declan G.
Abstract : Objectives: To compare patterns of care and peri‐operative outcomes of robot‐assisted radical prostatectomy (RARP) with other surgical approaches, and to create an economic model to assess the viability of RARP in the public case‐mix funding system. Patients and Methods: We retrospectively reviewed all radical prostatectomies (RPs) performed for localized prostate cancer in Victoria, Australia, from the Victorian Admitted Episode Dataset, a large administrative database that records all hospital inpatient episodes in Victoria. The first database, covering the period from July 2010 to April 2013 ( n = 5 130), was used to compare length of hospital stay (LOS) and blood transfusion rates between surgical approaches. This was subsequently integrated into an economic model. A second database ( n = 5 581) was extracted to cover the period between July 2010 and June 2013, three full financial years, to depict patterns of care and make future predictions for the 2014–2015 financial year, and to perform a hospital volume analysis. We then created an economic model to evaluate the incremental cost of RARP vs open RP (ORP) and laparoscopic RP (LRP), incorporating the cost‐offset from differences in LOS and blood transfusion rate. The economic model constructs estimates of the diagnosis‐related group (DRG) costs of ORP and LRP, adds the gross cost of the surgical robot (capital, consumables, maintenance and repairs), and manipulates these DRG costs to obtain a DRG cost per day, which can be used to estimate the cost‐offset associated with RARP in comparison with ORP and LRP. Economic modelling was performed around a base‐case scenario, assuming a 7‐year robot lifespan and 124 RARPs performed per financial year. One‐ and two‐way sensitivity analyses were performed for the four‐arm da Vinci SHD, Si and Si dual surgical systems (Intuitive Surgical Ltd, Sunnyvale, CA, USA). Results: We identified 5 581 patients who underwent RP in 20 hospitals in Victoria with an open, laparoscopic or robot‐assisted surgical approach in the public and private sector. The majority of RPs (4 233, 75.8%), in Victoria were performed in the private sector, with an overall 11.5% decrease in the total number of RPs performed over the 3‐year study period. In the most recent financial year, 820 (47%), 765 (44%) and 173 patients (10%) underwent RARP, ORP and LRP, respectively. In the same timeframe, RARP accounted for 26 and 53% of all RPs in the public and private sector, respectively. Public hospitals in Victoria perform a median number of 14 RPs per year and 40% of hospitals perform <10 RPs per year. In the public system, RARP was associated with a mean (±sd ) LOS of 1.4 (±1.3) days compared with 3.6 (±2.7) days for LRP and 4.8 (±3.5) days for ORP ( P < 0.001). The mean blood transfusion rates were 0, 6 and 15% for RARP, LRP and ORP, respectively ( P < 0.001). The incremental cost per RARP case compared with ORP and LRP was A442 and A2 092, respectively, for the da Vinci S model, A1 933 and A3 583, respectively, for the da Vinci Si model and A3 548 and A5 198, respectively for the da Vinci Si dual. RARP can become cost‐equivalent with ORP where 140 cases per year are performed in the base‐case scenario. Conclusions: Over the period studied, RARP has become the dominant approach to RP, with significantly shorter LOS and lower blood transfusion rate. This translates to a significant cost‐offset, which is further enhanced by increasing the case volume, extending the lifespan of the robot and reductions in the cost of consumables and capital.